2017
DOI: 10.1016/j.jtumed.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The decision of breastfeeding practices among parents attending primary health care facilities in suburban Malaysia

Abstract: Objectives This study aimed to determine the association between decision making for breastfeeding practices and associated factors for exclusive breastfeeding practices among parents attending primary health care facilities. Methods This cross-sectional study involved 196 parents who attended primary health care facilities in suburban Malaysia. A self-administered questionnaire was given to assess decision-making styles and factors associated with exclusive breastfeedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
5
0
3
Order By: Relevance
“…Ibu multipara meningkatkan kemungkinan untuk memberikan ASI eksklusif daripada ibu primipara (b= 1.72; CI 95%= 0.57 hinga 2.86; p= 0.003). Hasil penelitian ini sesuai dengan penelitian (Draman et al, 2017), yang menyatakan bahwa ibu dengan paritas lebih dari 1 kali memiliki kemungkinan 29.13 kali lebih besar untuk memberikan ASI eksklusif daripada ibu dengan paritas kurang dari 1 kali (OR= 29.13; CI 95%= 9.63 hingga 88.12). Ibu yang memiliki paritas lebih dari 1 kali telah memiliki pengalaman menyusui sebelumnya sehingga cenderung lebih baik dalam memberikan ASI eksklusif kepada bayinya.…”
Section: Pengaruh Paritas Terhadap Pemberian Asi Eksklusifunclassified
See 1 more Smart Citation
“…Ibu multipara meningkatkan kemungkinan untuk memberikan ASI eksklusif daripada ibu primipara (b= 1.72; CI 95%= 0.57 hinga 2.86; p= 0.003). Hasil penelitian ini sesuai dengan penelitian (Draman et al, 2017), yang menyatakan bahwa ibu dengan paritas lebih dari 1 kali memiliki kemungkinan 29.13 kali lebih besar untuk memberikan ASI eksklusif daripada ibu dengan paritas kurang dari 1 kali (OR= 29.13; CI 95%= 9.63 hingga 88.12). Ibu yang memiliki paritas lebih dari 1 kali telah memiliki pengalaman menyusui sebelumnya sehingga cenderung lebih baik dalam memberikan ASI eksklusif kepada bayinya.…”
Section: Pengaruh Paritas Terhadap Pemberian Asi Eksklusifunclassified
“…Ibu yang bekerja menurunkan kemungkinan untuk memberikan ASI eksklusif daripada ibu yang tidak bekerja (b= -2.94; CI 95%= -3.99 hingga -1.88; p= 0.001). Hasil penelitian Draman et al (2017) menyatakan bahwa ibu yang bekerja memiliki kemungkinan 0.12 kali lebih kecil untuk memberikan ASI eksklusif daripada ibu yang tidak bekerja (OR= 0.12; CI 95%= 0.05 hingga 0.28). Hasil penelitian ini sejalan dengan penelitian Sariyanti (2015), yang menyatakan bahwa ada hubungan antara pekerjaan dengan pemberian ASI eksklusif.…”
Section: Pengaruh Pekerjaan Terhadap Pemberian Asi Eksklusifunclassified
“…However, for some young mothers, close relatives such as partners, mothers, mothers-in-law, and sisters were firstly being first sources to seek helps when young mothers find issues related to breastfeeding and infant feeding practice. Previous literature reported that grandmothers and fathers have a key role in the decision of breastfeeding and infant feeding practice in many countries (Bich et al, 2019;Draman et al, 2017).…”
Section: Social Supports and Barriers To Practice Breastfeedingmentioning
confidence: 99%
“…al. [22] stressed the need to address and acknowledge the important role of father in initiating and sustaining exclusive breastfeeding among health practitioners. The study revealed that parents' mutual decision was an important factor influencing exclusive breastfeeding practices among mothers.…”
Section: Introductionmentioning
confidence: 99%